Method of Selecting Gloves Based on Pressure on The Palms Using A Measuring Instrument with A Force Sensing Resistor - Ranu Tri Widodo; Lobes Herdiman; Susy Susmartini (Jurnal Ilmiah Teknik Industri, 2022)
Assembly is a common activity in manufacturing companies. The use of handtools during assembly creates pressure on the palms surface which can lead to injury. To reduce the risk of injury, operators need to use gloves as personal protective equipment. Regardless of the general function of the glove, the type of glove tends to be chosen specifically for each task. But there is no specific method to determine the right gloves for certain activities. It is important to know the effect of using gloves on the palms surface during work activities. So this study aims to design a measuring instrument that can determine the pressure on the palm surface during activities by wearing gloves. This is done in order to be able to choose the right gloves for assembly. The result shown that during assembly the areas on the palms receive different pressure. Areas of the palms that receive the greatest pressure are the distal phalanx, and proximal phalanx on the index, middle, ring and little fingers. Pressure on the palms surface differs depending on the type of glove used. This may be due to the thickness of the glove, the thinner the glove, the greater the pressure on the palms surface. Assembling the chair using leather gloves has the lowest pressure value compared to other gloves. The pressure value on the palms surface when wearing leather gloves during the assembly of the chair is 262.15 N, 40% lower than the assembly without using gloves.